2021
DOI: 10.3390/catal11121466
|View full text |Cite
|
Sign up to set email alerts
|

Protein Modifications: From Chemoselective Probes to Novel Biocatalysts

Abstract: Chemical reactions can be performed to covalently modify specific residues in proteins. When applied to native enzymes, these chemical modifications can greatly expand the available set of building blocks for the development of biocatalysts. Nucleophilic canonical amino acid sidechains are the most readily accessible targets for such endeavors. A rich history of attempts to design enhanced or novel enzymes, from various protein scaffolds, has paved the way for a rapidly developing field with growing scientific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 154 publications
0
6
0
Order By: Relevance
“…28 It boosts catalytic and electrochemical properties while also providing biocompatibility. [29][30][31] The electrochemical H 2 O 2 biosensors found in recent literature generally do not show high sensitivity and have very low stability. These biosensors struggle to maintain a consistent sensor response for more than a week.…”
Section: Introductionmentioning
confidence: 99%
“…28 It boosts catalytic and electrochemical properties while also providing biocompatibility. [29][30][31] The electrochemical H 2 O 2 biosensors found in recent literature generally do not show high sensitivity and have very low stability. These biosensors struggle to maintain a consistent sensor response for more than a week.…”
Section: Introductionmentioning
confidence: 99%
“…Several excellent reviews have been published on industrial biocatalysis covering various aspects of enzymatic transformations for drug development. ,, As such, this perspective does not aim to be comprehensive but rather highlight the current state-of-the-art of preparative enzymatic synthesis in an industrial setting. Therefore, the use of biocatalysis for small-scale pharmaceutical metabolite synthesis, lead diversification, ,,, bioconjugation, and selective protein modification will not be focused upon in this article.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have demonstrated that the modification of the surface of functional proteins can modulate their native activity [5–7] . The modification of the primary sequence of the protein can give rise to several scenarios: from the complete inactivation of the protein to a significant enhancement of its performance.…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] Several reports have demonstrated that the modification of the surface of functional proteins can modulate their native activity. [5][6][7] The modification of the primary sequence of the protein can give rise to several scenarios: from the complete inactivation of the protein to a significant enhancement of its performance. Among all the combinations of functional proteins and artificial materials, the particular case of enzymes modified with polymers requires detailed investigation.…”
Section: Introductionmentioning
confidence: 99%